Ідеї творення великого турецького дастана - Більгін Топчу (Народна творчість та етнографія, 2010)
Anatolianism is an idea that formed by nationalistic approaches which supported by social and political conditions. Anatolinists who consider themselves as more realistic comparing to Pro Turkics, believe that reconstruction period of the societies can help the progress in mıch better way with certain social dynamics. In order to happen, real ideas which is derived from daily life dynamics is needed more than utopias. Hilmi Ziya Ulken is one of the biggest names of the intellectuals who think that way. He considers the epics which are one of the richest form of anonymous litetarature, as best way to understand the society and best tool to express the ideas. The epics are very special products that both make the people realize the value of it and become resources for the progress in modern literature. With these ideas, Hilmi Ziya had paid very special attention to the epics and followed the researches made on this subject. He also supported the people around him who can write an epics, besides even himself, attempted to write some… In this research, Hilmi Ziya’s special attention to the epics and his writing attempts are subjected.